(untitled) (Indian Journal of Public Health Research & Development, 2020)
Convenience food industry has shown a rapid growth in India in the last few years. Now a days they are very much in demand and is growing at a rapid rate. These foods are saviour for busy and working people. They have been widely accepted by the non-working people as well. Due to fast and busy life, consumption pattern of people is drifting from raw food to convenience foods. Convenience foods are overly processed food which saves the preparation and cooking time of food in the kitchen.. Young generation children are more likely to consume packaged food as they give great aroma, texture and taste. These foods determine the food choices and consumption pattern of the consumers. Urbanisation and the changing lifestyle has a huge role in increasing the demand of such food items. They are gaining immense popularity in the food industry, global food market and among the food scientists. In the past few years convenience food has shown a remarkable growth in the food market . This present study aims at studying the consumption pattern of convenience food in India.